Measurement of the Mass and Rigidity of Adsorbates on a Microcantilever Sensor - Javier Tamayo; A. Zaballos; Johann Mertens; Montserrat Calleja; Daniel Ramos (Sensors, 2007)
When microcantilevers are used in the dynamic mode, the resonance shift uponmaterial adsorption depends on the position of the adsorbate along the microcantilever. Wehave previously described that the adsorbate stiffness needs to be considered in addition toits mass in order to correctly interpret the resonance shift. Here we describe a method thatallows obtaining the Young’s modulus of the adsorbed bacteria derived from themeasurement of the frequency shift when adsorbates are placed close to the clampingregion. As a model system we have used E. Coli bacteria deposited on the cantileversurface by the ink-jet technique. We demonstrate that the correct information aboutadsorbed mass can be extracted by recording the cantilever profile and its resonanceresponse. Also, the position and extent of adsorbates is determined by recording themicrocantilever profile. We use a theoretical model based on the Euler – Bernouilliequation for a beam with both mass and flexural rigidity local increase due to the depositedmaterial.